Peranan Sekolah Dalam Menerapkan Pendidikan Akhlak Pada Siswa di SDN 10 Sungai Pasak Kec. Pariaman Timur - Dertha Mukhtar; Defri Mukhtar (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This research was conducted through observation and interview techniques, data processing techniques by examining the data obtained, reviewing the data in depth and drawing conclusions, data analysis techniques by adjusting the statements put forward by respondents to the problems studied. The results of the research that the authors get are the activities that the school does in implementing moral education for students at SDN 10 Sungai Pasak, East Pariaman District, all students take part in all activities carried out by the school in order to foster student morals. The school's actions against students who commit violations at SDN 10 Sungai Pasak, East Pariaman District are calling students with problems, asking students' habits, being given directions, being given advice, giving educational punishments, and calling parents of students. Supporting factors for policy makers in implementing moral education are the existence of qualified teachers, extracurricular activities for Islamic religious education outside school hours and competitions. The barrier factors for policy makers in implementing moral education are environmental factors where students live, the magnitude of the influence of technology, the lack of learning time and the lack of religious books for student reading.